2009
DOI: 10.1097/scs.0b013e3181abb116
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Nerve Injuries of the Pediatric Hand: Issues in Diagnosis and Management

Abstract: Peripheral nerve injuries resulting in significant neural disruption frequently present complex management challenges. Typically the product of fracture, dislocation, or crush injuries, pediatric peripheral nerve injuries may be difficult to accurately characterize. Thorough clinical examination coupled with electromyogram and neurophysiologic studies are extremely useful. When possible, primary repair should be attempted. If, however, defect size precludes primary reanastomosis, use of a nerve graft may be ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…Some studies have suggested that repair within 24 hours of injury is optimal, with others finding no association between time and patient outcome. 5,8 Our study did not find a statistically significant relationship between time to repair and sensorimotor recovery. Given that our patients received primary repair at a mean of 2.3 days (0-8), it is reasonable to assert that repair within 48 hours of injury is sufficient for optimal recovery.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Some studies have suggested that repair within 24 hours of injury is optimal, with others finding no association between time and patient outcome. 5,8 Our study did not find a statistically significant relationship between time to repair and sensorimotor recovery. Given that our patients received primary repair at a mean of 2.3 days (0-8), it is reasonable to assert that repair within 48 hours of injury is sufficient for optimal recovery.…”
Section: Discussioncontrasting
confidence: 75%
“…Primary surgical repairs should be attempted where possible; however, contamination, bony instability, and compromised tissue viability may preclude this, requiring delayed secondary repair. 5 Due to the infrequency of this type of injury in the pediatric population, data on long-term outcomes and prognostic indicators are lacking in the literature. Studies on the adult population have found that increasing age and smoking are factors associated with poor recovery following nerve repair; however, these data are not available for the pediatric population and some adult prognostic indicators are not applicable to children.…”
Section: Introductionmentioning
confidence: 99%
“…Autologous vein segment graft as a nerve conduit has been established as an effective treatment for the repair of nerve gaps less than 3 cm [29, 30]; it is used in hand surgery [31] and in pediatrics [32]. In a recent study [33], histomorphological examination of the sections proximal to, from, and distal to the repair zone over three months revealed less epineural scarring, a thinner epineurium, more regenerated axons and fewer inflammatory cells in groups where vein grafting was used, because the vein graft provided additional mechanical and chemical support in the size discrepancy of the nerve regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of wrinkles in the injured digit would indicate nerve damage. 12 Parents can be instructed to look for this phenomenon in the bathtub at home.…”
Section: Assessmentmentioning
confidence: 99%